2017
DOI: 10.18203/issn.2455-4510.intjresorthop20171575
|View full text |Cite
|
Sign up to set email alerts
|

A study to assess epidemiological, clinical profile and outcome of Monteggia fracture dislocation in adults: a retrospective study

Abstract: <p class="abstract"><strong>Background:</strong> Among all the forearm fractures Monteggia fractures account for approximately 1-2%. Early recognition with anatomical reduction and stable internal fixation is most important in the management of Monteggia fractures. This study was performed to evaluate clinical profile and functional outcome of Monteggia fracture dislocation<span lang="EN-IN">.</span></p><p class="abstract"><strong>Methods:</strong> This ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
3
0
1
Order By: Relevance
“…The mean age of the patients was 35.96±11.48 years where minimum age was 20 years and maximum age was 55 years. Retrospective study conducted in India among adult patients showed similar result [7]. Eighty percent patients of this study were male which was consistent with other studies [6][7][8].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The mean age of the patients was 35.96±11.48 years where minimum age was 20 years and maximum age was 55 years. Retrospective study conducted in India among adult patients showed similar result [7]. Eighty percent patients of this study were male which was consistent with other studies [6][7][8].…”
Section: Discussionsupporting
confidence: 90%
“…Retrospective study conducted in India among adult patients showed similar result [7]. Eighty percent patients of this study were male which was consistent with other studies [6][7][8]. This fracture often occurs after a highway accident or aggression, which explains the male predominance of age.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations